Techno-economic study on reagents consumption during uranium leaching, a case study: Gattar pilot plant, Egypt. Issue 1 (1st January 2021) - Nagar, Mohamed Soliman
Abstract: As a techno–economic study, column and vat leaching experiments of low-grade uranium mineralization were implemented to obtain a deep understanding of reagent consumption during the uranium leaching stage. The leaching index (β) is a techno-economical parameter that must be considered during the decision-making stage of project development in order to arrive at an optimal point based on solution consumption and recovery. The results indicate that 21.2 and 32 g of acid are consumed using an acid concentration of 20 and 40 g/L, respectively, to have a 1% increase in the uranium recovery. Also, 1.0 and 1.8 L solutions using 0.1:1 and 0.2:1 sprinkling intensities are consumed, respectively, to have a 1% increase in the uranium recovery during column leaching period. The results of the leaching index (β) of vat leaching indicate that 4.1 m 3 solution and 88 kg acid are consumed to have a 1% increase in the uranium recovery after 90 day. The overall consumed acid after this period was 17.6 kg/ton of ore.